2011
DOI: 10.1186/1471-2334-11-200
|View full text |Cite
|
Sign up to set email alerts
|

In vaginal fluid, bacteria associated with bacterial vaginosis can be suppressed with lactic acid but not hydrogen peroxide

Abstract: BackgroundHydrogen peroxide (H2O2) produced by vaginal lactobacilli is generally believed to protect against bacteria associated with bacterial vaginosis (BV), and strains of lactobacilli that can produce H2O2 are being developed as vaginal probiotics. However, evidence that led to this belief was based in part on non-physiological conditions, antioxidant-free aerobic conditions selected to maximize both production and microbicidal activity of H2O2. Here we used conditions more like those in vivo to compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
284
1
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(299 citation statements)
references
References 32 publications
4
284
1
10
Order By: Relevance
“…Furthermore, O'Hanlon et al presented compelling evidence suggesting that if measurements of vaginal secretions are made under hypoxic conditions that mimic the vagina, pH is lower and lactic acid concentrations are higher than in data previously reported under aerobic conditions (76). Lactic acid may also prove to be more effective than acidity alone in preventing overgrowth of bacteria and acquisition of sexually transmitted organisms (77,78). Under aerobic conditions, some lactobacilli can produce hydrogen peroxide (another inhibitor of anaerobes and other organisms), but little if any hydrogen peroxide is detectable in vaginal secretions due to the hypoxic environment and the high antioxidant capacity of vaginal secretions (78,79).…”
Section: Bacterial Diversity Of the Human Vaginamentioning
confidence: 99%
“…Furthermore, O'Hanlon et al presented compelling evidence suggesting that if measurements of vaginal secretions are made under hypoxic conditions that mimic the vagina, pH is lower and lactic acid concentrations are higher than in data previously reported under aerobic conditions (76). Lactic acid may also prove to be more effective than acidity alone in preventing overgrowth of bacteria and acquisition of sexually transmitted organisms (77,78). Under aerobic conditions, some lactobacilli can produce hydrogen peroxide (another inhibitor of anaerobes and other organisms), but little if any hydrogen peroxide is detectable in vaginal secretions due to the hypoxic environment and the high antioxidant capacity of vaginal secretions (78,79).…”
Section: Bacterial Diversity Of the Human Vaginamentioning
confidence: 99%
“…Studies have shown that these communities can be divided into five different types, four of which are dominated by either Lactobacillus iners, Lactobacillus crispatus, Lactobacillus gasseri, or Lactobacillus jensenii (2). These four species are closely related and are thought to perform similar ecological functions in the vaginal environment (namely, the production of lactic acid) (3,4). Instances of cooccurrence among these species are rare, and temporal data have demonstrated that shifts in the dominant Lactobacillus are common (5), suggesting that the species compete for shared niche space in the vagina.…”
mentioning
confidence: 99%
“…Weak organic acids (WOAs), primarily produced by anaerobic bacteria via fermentation of undigested complex carbohydrates, are among the most abundant metabolites found on mucosal surfaces and the lumen of the gut (16). Vaginal lactobacilli secrete large amounts of lactic acid (ϳ55 to 111 mM), concomitantly lowering the mucosal pH to ϳ4.5 (17,18). Short-chain fatty acids (SCFAs), such as acetic, propionic, and butyric acid, are produced by a large spectrum of GI bacteria and reach total concentrations of up to 140 mM (16,19).…”
mentioning
confidence: 99%